1981
DOI: 10.1071/bt9810247
|View full text |Cite
|
Sign up to set email alerts
|

Isozymes, secondary compounds and experimental cultures of Australian seagrasses in Halophila, Halodule, Zostera, Amphibolis and Posidonia

Abstract: Systematic and ecological implications were shown for Australian seagrasses by studies of isozymes, secondary compounds and experimental cultures. In Halophila, small- and large-leaved plants which occur sympatrically from northern Queensland to New South Wales and were referred to H. ovalis (R.Br.) Hook. f. differed in isozymes and secondary compounds and maintained leaf size differences in experimental cultures. The small-leaved plants should be referred to a different species. In Halodule, narrow-leaved pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1983
1983
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…A similar approach in temperate Australia by Nicholls et al (1982) showed that the lipids, comprising up to 7.6% dry weight, of P. australis and Heterozostera tasmanica, had patterns of monocarboxylic, dicarboxylic and hydroxy acids sufficiently different to allow even detritus of these two species to be distinguished. Taxonomic questions at the species level in seagrasses have also been approached chemically by McMillan et al (1981) and McMillan (1983) using secondary products such as the flavonones and their sulphonated derivatives from Amphibolis, Halodule, Halophila, Posidonia and Zostera.…”
Section: Secondary Metabolites and Chemotaxonomymentioning
confidence: 99%
“…A similar approach in temperate Australia by Nicholls et al (1982) showed that the lipids, comprising up to 7.6% dry weight, of P. australis and Heterozostera tasmanica, had patterns of monocarboxylic, dicarboxylic and hydroxy acids sufficiently different to allow even detritus of these two species to be distinguished. Taxonomic questions at the species level in seagrasses have also been approached chemically by McMillan et al (1981) and McMillan (1983) using secondary products such as the flavonones and their sulphonated derivatives from Amphibolis, Halodule, Halophila, Posidonia and Zostera.…”
Section: Secondary Metabolites and Chemotaxonomymentioning
confidence: 99%
“…An isozyme study of Halodule showed a clear difference between samples from the western tropical Atlantic and the Indo-Pacific (McMillan et al 1981, McMillan 1991. A molecular phylogeny based on the ITS of nDNA also showed two clusters, one from the western tropical Atlantic and the other from the western Pacific (Waycott & Barnes unpublished).…”
Section: Systematics and Evolution Of Halodulementioning
confidence: 99%
“…It is common knowledge that fruits, vegetables, and other plants are a rich source of vitamins, minerals, and bioactive secondary metabolites (metabolic products that are not necessary for growth, development, and reproduction, but are essential for ecological and other interactions), many of which have anti-inflammatory properties [ 7 , 8 ]. In addition to commonly consumed plant materials, phytochemical analyses of many seagrasses including Halophila stipulacea [ 9 ], Thalassodendron ciliatum [ 9 ], Halodule uninervis [ 9 ], Halodule pinifolia [ 10 , 11 ], Halophila ovalis [ 10 ], Syringodium isoetifolium [ 10 , 11 ], Thalassia hemprichii [ 11 , 12 ], Cymodocea rotundata [ 11 ], Enhalus acoroides [ 11 ], Cymodocea serrulate [ 11 ], and Zostera muelleri [ 13 , 14 ] have indicated seagrasses are also natural reservoirs of phenolics, flavonoids, sterols, alkaloids, saponins, tannins, terpenoids, and other bioactive secondary metabolites.…”
Section: Introductionmentioning
confidence: 99%